Beyond global mobility: how human capital shapes the MNE in the 21st century - Minbaeva, Dana; Narula, Rajneesh; Phene, Anupama; Fitzsimmons, Stacey (Journal of International Business Studies, 2025)
The global mobility of people has transformed how multinational enterprises (MNEs) manage and benefit from multiple locations. We examine the changing locational boundedness of human capital with globalization and how this has impacted the competitiveness of MNEs. The growing use of quasi-internalization through the active reliance on global value chains and outsourcing has altered the way MNEs spatially organize their activities to optimize their access to human capital, a key source of ownership advantages. We identify areas for further research, including new strategies for managing human resources using these new forms of cross-border governance. Collectively, the papers in this special issue provide insights into how MNEs can leverage the movement and reorganization of their human capital to enhance their unique capabilities and succeed in international business.